2017
DOI: 10.1371/journal.pone.0186273
|View full text |Cite
|
Sign up to set email alerts
|

Further insight into genetic variation and haplotype diversity of Cherry virus A from China

Abstract: Cherry virus A (CVA) infection appears to be prevalent in cherry plantations worldwide. In this study, the diversity of CVA isolates from 31 cherry samples collected from different orchards around Bohai Bay in northeastern China was analyzed. The complete genome of one of these isolates, ChYT52, was found to be 7,434 nt in length excluding the poly (A) tail. It shares between 79.9–98.7% identity with CVA genome sequences in GenBank, while its RdRp core is more divergent (79.1–90.7% nt identity), likely as a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 38 publications
5
24
0
Order By: Relevance
“…Where multiple strains of a species were identified, considerable genetic diversity was observed amongst the strains. As reported in other studies [18,72,76,[80][81][82], these virus species were often distributed throughout their individual phylogenetic trees, rather than forming a single Australian cluster, and were related to overseas isolates originating from different regions. This suggests multiple introductions of each virus species into Australia.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Where multiple strains of a species were identified, considerable genetic diversity was observed amongst the strains. As reported in other studies [18,72,76,[80][81][82], these virus species were often distributed throughout their individual phylogenetic trees, rather than forming a single Australian cluster, and were related to overseas isolates originating from different regions. This suggests multiple introductions of each virus species into Australia.…”
Section: Discussionsupporting
confidence: 73%
“…All the Australian recombinant isolates shared similar phylogenetic groupings with their major parental sequence which indicates close genetic connectivity within the population of these recombinants. Previous studies have shown frequent recombination events between multiple divergent virus genetic strains occurring in individual plants [79,81]. Interestingly, no recombinants were observed in the six Prunus trees that had multiple full-genome genetic strains of CVA, CGRMV and LChV1.…”
Section: Discussionmentioning
confidence: 84%
“…Cherry virus A (CVA) was first described from sweet cherry in Germany by Jelkman [ 29 ]. Since that time, this capillovirus (genus in the Betaflexivirideae family) has been reported all over the world and was found to be frequent on the sweet and sour cherry [ 30 , 31 ]. Moreover, it was detected in several Prunus hosts (apricot, peach, plum, Japanese apricot) as well [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its detection is not possible either by biological indexing or by ELISA. With the appearance of NGS, it is often reported to be present in mixed infections, together with other well-known fruit tree-infecting viruses, making it difficult to correlate its presence with the occurring symptoms [ 30 , 31 ]. Although it is considered to be latent, it cannot be ruled out that the severity of symptoms can be affected by its presence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation